Safety of zinc chelate of methionine sulfate for the target species. (24th October 2018) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Zinc chelate of methionine sulfate is intended to be used as a nutritional additive (functional group: compounds of trace elements). The additive is zinc chelated with methionine in a molar ratio 1:1. It is intended to supply zinc as a nutritional additive to all animal species/categories. In 2017, the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) adopted an opinion on the safety and efficacy of zinc chelate of methionine sulfate for all animal species. In that opinion, the Panel could not conclude on the safety of the additive for the target species. The Commission gave the applicant the possibility of submitting additional information to allow the FEEDAP Panel to complete its assessment. For this reason, additional data have been provided related to the safety of the additive for the target species and this new information is the subject of this opinion. The new tolerance study on chickens for fattening has been assessed; the results of this study indicate that the additive does not promote adverse effects in the birds as compared to an inorganic source of zinc (zinc oxide). The FEEDAP Panel concluded that the additive under assessment 'zinc chelate of methionine sulfate' is safe for chickens for fattening when used up to the maximum content of zinc in complete feed authorised in the EU; this conclusion is extended to all animal species.